Mainstar MS/VCR : the tool for efficient device cloning - Lovelace, Mary (IBM redbooks., 2005)
MS/VCR provides a fast, reliable facility with high integrity for the renaming and recataloging of data sets on target volumes after a FlashCopy or Snapshot volume copy, solving the cloned data access dilemma. This facility enables the immediate use of the data from the same system as the original copy. MS/VCR resolves catalog conflicts of like-named datasets that are created by "cloning" a volume. It also solves internal conflicts that are created when copying a volume to a different VOLSER. MS/VCR is designed to rename and catalog target volume datasets in record time. The window of time required to copy and rename a target dataset is a critical factor for many customers. This IBM Redbooks publication provides a broad understanding of the MS/VCR product and how to use it in real situations.